AGE BOUNDARIES AND GEODYNAMIC NATURE OF THE KAAKHEM POLYCHRONOUS BATHOLITH, EASTERN TUVA - Rudnev S.N.; Vladimirov A.G.; Vladimirov V.G.; Shintyapin B.N.; Ponomarchuk V.A.; Bibikova E.V. (My University, 2004)
In this paper based on the study of the Kaakhem polychronous batholith, the largest (≥3000 km2) structure in the ASFB Altai-Sayan fold system, we attempted to correlate the geological observations with U-Pb and Ar-Ar isotopic data on petrographic varieties, to estimate scales and compositional features of different-aged magmatic complexes, and intepret their geodynamic setting.